2020
DOI: 10.1038/s41598-020-68669-w
|View full text |Cite
|
Sign up to set email alerts
|

Identification of spin effects in the anomalous Righi–Leduc effect in ferromagnetic metals

Abstract: According to Eqs. (4) and (5), heat current density can be determined by spin current and temperature gradient as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
2
0
1
Order By: Relevance
“…За последние годы появился ряд экспериментальных работ, в которых обнаруженные эффекты спинтроники и спинкалоритроники еще не получили объяснения: управление направлением потока тепла магнитнотермоэлектрическим эффектом в деформированном металлическом магнетике [8], расширение температурного диапазона накачки тепла с помощью эластокалорического эффекта [9], аномальный эффект Риги−Ледюка в ферромагнитных материалах [10]. Представленная в работе модель может лечь в основу теории новых эффектов.…”
Section: гдеunclassified
“…За последние годы появился ряд экспериментальных работ, в которых обнаруженные эффекты спинтроники и спинкалоритроники еще не получили объяснения: управление направлением потока тепла магнитнотермоэлектрическим эффектом в деформированном металлическом магнетике [8], расширение температурного диапазона накачки тепла с помощью эластокалорического эффекта [9], аномальный эффект Риги−Ледюка в ферромагнитных материалах [10]. Представленная в работе модель может лечь в основу теории новых эффектов.…”
Section: гдеunclassified
“…Let us average vector J (10) in the macroscopic region over random crystallite orientations. It is convenient to express the rotation matrix via Euler angles.…”
mentioning
confidence: 99%
“…During recent years there were published a number of experimental studies where the revealed spintronics and spin−caloritronics effects have not yet been explained: strain−induced switching of the heat flux direction due to magneto−thermoelectric effect in a magnetic metal [8], extension of the heat pump temperature range due to the elastocaloric effect [9], and anomalous Righi-Leduc effect in ferromagnetic materials [10]. The model presented in this paper may be used as a basis for theoretical description of those new effects.…”
mentioning
confidence: 99%